2022
DOI: 10.1007/s13235-022-00450-2
|View full text |Cite
|
Sign up to set email alerts
|

Q-Learning in Regularized Mean-field Games

Abstract: In this paper, we introduce a regularized mean-field game and study learning of this game under an infinite-horizon discounted reward function. Regularization is introduced by adding a strongly concave regularization function to the one-stage reward function in the classical mean-field game model. We establish a value iteration based learning algorithm to this regularized mean-field game using fitted Q-learning. The regularization term in general makes reinforcement learning algorithm more robust to the system… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(6 citation statements)
references
References 55 publications
0
5
0
Order By: Relevance
“…Hence assumption (d) is not true for this new formulation. To handle this problem, a common approach is to add a strongly convex regularization term to the cost function cnew (see [3]). In regularized version, the cost function is given by creg (x, u, z) := cnew (x, u, z) + λ h(u) where h is a θ-strongly convex function and λ > 0 is some constant.…”
Section: Computing Equilibrium Of Gnepmentioning
confidence: 99%
“…Hence assumption (d) is not true for this new formulation. To handle this problem, a common approach is to add a strongly convex regularization term to the cost function cnew (see [3]). In regularized version, the cost function is given by creg (x, u, z) := cnew (x, u, z) + λ h(u) where h is a θ-strongly convex function and λ > 0 is some constant.…”
Section: Computing Equilibrium Of Gnepmentioning
confidence: 99%
“…Similar to Remark 2.2, when (2.7) holds, the stationary equilibrium concept in Definition 2.2 aligns with the conventional stationary equilibrium in time-consistent MFGs under the infinite horizon setting. This concept has been widely studied in the related literature, e.g., [20,1,3,29]. Now we characterize an MFG equilibrium in Definition 2.1 as a fixed point of the operator Φ ν below.…”
Section: Mean Field Games With Time-inconsistencymentioning
confidence: 99%
“…First, it has been shown that an equilibrium in the (time-consistent) MFG can serve as an approximate equilibrium in the (time-consistent) N -agent game when N is large enough; see, e.g. [13,26,3]. Secondly, efforts have also been made to show that equilibria in (time-consistent) N -agent games can approach an equilibrium in the (time-consistent) MFG as N tends to infinity; see, e.g., [18,22,23,17,6,12,5,4].…”
Section: Introductionmentioning
confidence: 99%
“…With the exception of [Angiuli et al, 2022b], which is the basis of the present paper, these methods focus on solving one of the two types of problems, MFG or MFC. On the one hand, to learn MFGs solutions, two classical families of methods are those relying on strict contraction and fixed point iterations (e.g., [Guo et al, 2019, Cui and Koeppl, 2021, Anahtarci et al, 2023 with tabular Qlearning or deep RL), and those relying on monotonicity and the structure of the game (e.g., , Perrin et al, 2020, Laurière et al, 2022 using fictitious play and tabular or deep RL). Two-timescale analysis to learn MFG solutions has been used in [Mguni et al, 2018, Subramanian andMahajan, 2019].…”
Section: Introductionmentioning
confidence: 99%